Analisis Strategi Pemasaran Agen dalam Mempertahankan Loyalitas Nasabah di PT BRI Life Syariah Cabang Gatot Subroto - Muhammad Risalah Harahap; Rahmi Syahriza (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Bri Life Syariah branch of Gatot Subroto is one of the companies engaged in insurance. In an effort to increase sales of insurance policies in Medan City generally use several marketing strategies. The marketing strategy is implemented by the insurance agent/consultant of the company. This type of research is descriptive with a qualitative approach. Data collection used by using interviews, study documentation and observation. The study in this research is to find out "Agent Marketing Strategy in Maintaining Customer Loyalty at PT. Bri Life Syariah branch of Gatot Subroto with research aspects: insurance products, premium prices, promotions, places, people and physical facilities. The results showed that the branch of PT. Bri Life Syariah Gatot Subroto branch has been able to carry out the marketing strategy created and determined by the company through several patterns, namely moving its agents/consultants to the maximum in the field with adequate knowledge about insurance products and benefits so that they have the ability to explain them to potential customers/prospective consumers and marketing patterns Online through the company's website which is promoted through various electronic media. The technical marketing of various types of insurance owned by the company is done by moving agents/consultants to visit from house to house (door to door). communities that have been targeted by agents/consuls previously. The second technique is to hold meetings with groups of people both in offices and plantation companies and other economic institutions so that the sale of policies can be done collectively. Thus the branch company PT. Bri Life Syariah Gatot Subroto branch managed to increase sales of insurance policies from the previous year, namely 2017.